Feminist Disruptions in Mexican Art, 1975 - 1987 - Giunta, Andrea Graciela (2013)
Between 1975 and 1987 feminism in the arts in Mexico delineated a unique situation, one without parallel in the panorama of Latin American art. In a group of exhibitions, works and texts, women's place in Mexican art was critically analyzed, unfolding a broad map of positions. Although a chronology and list of names of the artists who shaped this scenario have been established, the intervention that each work proposed in the debate on women's place and the feminine that gained visibility during those years has not yet been examined. Based on a situated analysis of these works, this article proposes to discuss these works' intervention in configuring how the debate on artistic feminism took shape during this period in Mexico.